The Thirty-Day Mortality Rate and Nephrotoxicity Associated With Trough Serum Vancomycin Concentrations During Treatment of Enterococcal Infections: A Propensity Score Matching Analysis - Katip, Wasan; Okonogi, Siriporn; Oberdorfer, Peninnah (Frontiers in Pharmacology, 2022)
The objective of this study was to evaluate the relationship between vancomycin trough levels in patients with documented enterococcal infections and mortality, clinical outcomes, microbiological outcomes and nephrotoxicity. We conducted a retrospective cohort study of patients with enterococcus infections who were prescribed vancomycin with therapeutic drug monitoring during January 2010 and December 2019 at Chiang Mai University Hospital (CMUH). The study enrolled 300 participants who met the inclusion criteria and were prescribed vancomycin with therapeutic drug monitoring. The results of this study showed that, after propensity score matching, a vancomycin trough of ≥ 15 mg/L was associated with significant differences in 30-day mortality compared to a vancomycin trough of < 15 mg/L (aHR: 0.41, 95% CI: 0.21–0.82; p = 0.011). Likewise, a vancomycin trough of ≥ 15 mg/L was associated with significant differences in the clinical response (aHR: 0.49, 95% CI: 0.26–0.94; p = 0.032), microbiological response (aHR: 0.32, 95% CI: 0.12–0.87; p = 0.025) and nephrotoxicity (aHR: 3.17, 95% CI: 1.39–7.23; p = 0.006), com-pared with a vancomycin trough of < 15 mg/L. However, sub-group analysis found that very high trough levels (> 20 mg/L) were also associated with a high rate of nephrotoxicity (aHR: 3.55, 95% CI 1.57–8.07, p = 0.002), when compared with a vancomycin trough of < 15 mg/L. The target vancomycin trough concentration was ≥ 15 mg/L and this target can be an optimal alternative to the use of area under the curve (AUC) values for monitoring the treatment of enterococcal infection.